Characterization of the 163Ho electron capture spectrum: a step towards the electron neutrino mass determination - Ranitzsch, Philipp; Velte, Clemens; Wegner, Mathias; Hengstler, Daniel; Kempf, Sebastian; Fleischmann, Andreas; Enss, Christian; Gastaldo, Loredana (Physical review letters, 2017)
The isotope 163Ho is in many ways the best candidate to perform experiments to investigate the value of the electron neutrino mass. It undergoes an electron capture process to 163Dy with an energy available to the decay, QEC, of about 2.8 keV. According to the present knowledge, this is the lowest QEC value for such transitions. Here we discuss a newly obtained spectrum of 163Ho, taken by cryogenic metallic magnetic calorimeters with 163Ho implanted in the absorbers and operated in anticoincident mode for background reduction. For the first time, the atomic deexcitation of the 163Dy daughter atom following the capture of electrons from the 5s shell in 163Ho, the OI line, was observed with a calorimetric measurement. The peak energy is determined to be 48 eV. In addition, a precise determination of the energy available for the decay QEC=(2.858±0.010stat±0.05syst) keV was obtained by analyzing the intensities of the lines in the spectrum. This value is in good agreement with the measurement of the mass difference between 163Ho and 163Dy obtained by Penning-trap mass spectrometry, demonstrating the reliability of the calorimetric technique.
Im Titel ist die Zahl 163 hochgestellt
Gesehen am 26.03.2018